Food carbohydrate chemistry - Wrolstad, Ronald E., 1939- (Wiley-Blackwell, 2012)
"Not since "Sugar Chemistry" by Shallenberger and Birch (1975) has a text clearly presented and applied basic carbohydrate chemistry to the quality attributes and functional properties of foods. Now in Food Carbohydrate Chemistry, author Wrolstad emphasizes the application of carbohydrate chemistry to understanding the chemistry, physical and functional properties of food carbohydrates. Structure and nomenclature of sugars and sugar derivatives are covered, focusing on those derivatives that exist naturally in foods or are used as food additives. Chemical reactions emphasize those that have an impact on food quality and occur under processing and storage conditions. Coverage includes: how chemical and physical properties of sugars and polysaccharides affect the functional properties of foods; taste properties and non-enzymic browning reactions; the nutritional roles of carbohydrates from a food chemist's perspective; basic principles, advantages, and limitations of selected carbohydrate analytical methods. An appendix includes descriptions of proven laboratory exercises and demonstrations. Applications are emphasized, and anecdotal examples and case studies are presented. Laboratory units, homework exercises, and lecture demonstrations are included in the appendix. In addition to a complete list of cited references, a listing of key references is included with brief annotations describing their important features"-Resumé vydavatel
Keywords: sacharidy; potravinářství; carbohydrates; food industry and trade; elektronické knihy; sborníky; electronic books; papers of several authors